Muslim Gen Z Investment Decision: An Analysis Using Social Media Factors - Mega Noerman Ningtyas; Nur Laili Fikriah; Ayub Wijayati Sapta Pradana (Universitas Muhammadiyah Yogyakarta, 2024)
Seventy-one point five million (71,5 million or 26,4 percent) people in Indonesia are classified as Gen Z. Indonesia is the largest Muslim-majority country, with a significant portion of its population belonging to Gen Z. It is our concern to explore the potential of Muslim Gen Z. Furthermore, in the digital era, Muslim Gen Z’s investment decisions are increasingly influenced by social media where they can easily get various information. This study analyzes both the direct and indirect effects of social media, digital financial literacy, and investment decisions. We used a quantitative approach. Data were collected from 175 Gen Z investors through an online questionnaire and analyzed using path analysis with SEM-PLS. Our findings reveal that social media enhances digital financial literacy, which in turn positively affects investment decisions. Also, digital financial literacy enhances investment decisions among Muslim Gen Z. These results suggest that while social media can be a valuable resource for improving financial literacy, the reliability and depth of information from online communities may be insufficient for making informed investment decisions. Our study provides insights for investors to develop effective strategies and for policymakers to enhance financial education initiatives.